Impact of instagram on self-esteem among students in Northern University: a case study in UUM - Mustafa Khalid, Nur Izyan (2019)
Instagram is utilized each day universally and it is a more up to date free social networking site. It is an online versatile photograph sharing, video-sharing and social networking service that empowers its users to take pictures and recordings and offer them on various stages. Self esteem refers to both an individual’s affective feeling towards themselves (how much they like themselves) as well as their cognitive judgment of their own self-worth. This study was conducted through interview among selected students in Universiti Utara Malaysia (UUM). Focus of this study is the impact of Instagram on selfesteem in individual and the different on self-esteem between genders. The result shows many of the responses were positive feelings about themselves. Meanwhile, findings also show that there is a difference in self-esteem between the male and a female students which is female students has more self-esteem than male students. Social media play an important role in individual life. It is further pointed out that more current and future research is relevant to the use of social media and its importance to the development of one's self-esteem.